The mechanisms and control of mRNA turnover in eukaryotic cells - Parker, Roy (Henry Stewart Talks, 2007)
Control of mRNA degradation, Modulation in response to physiological cues, Mechanisms of mRNA turnover, Critical nucleases, Sequence-specific binding of regulators, Rates of turnover, mRNA decay and viral infections, Role in recognizing aberrant mRNAs
Archived at 2022/04/13